2003
DOI: 10.1242/dev.00401
|View full text |Cite
|
Sign up to set email alerts
|

XMAN1, an inner nuclear membrane protein, antagonizes BMP signaling by interacting with Smad1 inXenopusembryos

Abstract: A family of inner nuclear membrane proteins is implicated in gene regulation by interacting with chromatin, nuclear lamina and intranuclear proteins; however, the physiological functions of these proteins are largely unknown. Using a Xenopus expression screening approach with an anterior neuroectoderm cDNA library, we have identified an inner nuclear membrane protein, XMAN1, as a novel neuralizing factor that is encoded by theXenopus ortholog of human MAN1. XMAN1 mRNA is expressed maternally, and appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 73 publications
9
152
0
Order By: Relevance
“…One possibility is that loss of LBR expression directly affects the activities of a transcription factor that regulates gp91 phox gene expression. Several recent studies of other inner nuclear envelope proteins lend support to this notion; the Xenopus homolog of mammalian MAN1, XMAN1, was shown to block transcriptional regulation by bone morphogenetic protein, and LAP2β repressed the transcriptional activity of several transcription factors, including E2F family members p53 and NF-kB [38][39][40]. Multiple transcriptional regulators have been identified to positively regulate gp91 phox expression, including NF-kB, PU.1, C/EBPε and HoxA9 [41][42][43][44].…”
Section: Discussionmentioning
confidence: 91%
“…One possibility is that loss of LBR expression directly affects the activities of a transcription factor that regulates gp91 phox gene expression. Several recent studies of other inner nuclear envelope proteins lend support to this notion; the Xenopus homolog of mammalian MAN1, XMAN1, was shown to block transcriptional regulation by bone morphogenetic protein, and LAP2β repressed the transcriptional activity of several transcription factors, including E2F family members p53 and NF-kB [38][39][40]. Multiple transcriptional regulators have been identified to positively regulate gp91 phox expression, including NF-kB, PU.1, C/EBPε and HoxA9 [41][42][43][44].…”
Section: Discussionmentioning
confidence: 91%
“…In Xenopus embryos, the proposed MAN1 alleles named XMAN1 and SANE (Smad1 antagonistic effector) regulate dorsal-ventral axis determination (3,11,12). The C-terminal domain of XMAN1 antagonizes signaling by bone morphogenetic proteins by binding directly to Smad1, Smad5, or Smad8, which are downstream effectors of signal transduction pathways triggered when BMP-4 binds its receptor at the plasma membrane (3).…”
mentioning
confidence: 99%
“…Osada et al [2003] further demonstrated that the Xenopus MAN1 orthologue antagonized BMP signaling downstream of its receptor in animal cap development and BMP reporter gene activation assays. They also showed that the ectoderm neutralizing and BMP-antagonizing activities of MAN1 resided in the carboxyl-terminal region and that this region bound to Smad1, Smad5, and Smad8.…”
Section: Man1 Regulates Smad Signalingmentioning
confidence: 90%
“…MAN1 was also identified as a Smad1 binding protein that antagonizes BMP signaling in a functional screen for cDNAs that neutralized ectoderm formation in Xenopus development [Osada et al, 2003]. Osada et al [2003] further demonstrated that the Xenopus MAN1 orthologue antagonized BMP signaling downstream of its receptor in animal cap development and BMP reporter gene activation assays.…”
Section: Man1 Regulates Smad Signalingmentioning
confidence: 93%